PERAN KELOMPOK TANI DALAM USAHATANI PADI SAWAH DI DESA SEKERAT KECAMATAN BENGALON - Monika, Monika; Bustomi, Muhamad Yazid; Novita Dewi, Indah; Sukariyan, Sukariyan (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
The objectives of this study were to (1) determine the role of farmer groups in paddy rice farming, and (2) determine the level of motivation of farmers in participating in Tirta Benua farmer group activities in Sekerat Village. This research was conducted from April to July 2021 in Sekerat Village, Bengalon District, East Kutai Regency, East Kalimantan. Sampling for farmers used the saturated sample method or census with 47 rice paddy farmers as respondents. Data analysis was done using a quantitative descriptive analysis method, scoring, and a Likert scale. The study's results were the value of the role of farmer groups based on aspects of member cooperation, production units, and farm workability included in the high category. The motivation of farmers to participate in farmer group activities is seen from the aspects of economic aspects and sociological aspects. In the economic aspect, the percentage of farmer motivation is 84.7% which includes a very high category, while the percentage of sociological motivation is 90.5% which also includes a very high category.